Penerapan Syariat Islam dari Sudut Pandang Media dan Perempuan di Aceh - Maulina, Putri (Program Studi Ilmu Komunikasi FISIP Universitas Syiah Kuala, 2019)
The discourse of the Sharia implementation in Aceh in the context of media places women as the most reported group. Serambi Indonesia is one of the local print media that has intensively covered the enforcement of Sharia in Aceh. This study aims to look at the discourse of Sharia enforcement in local media and how the female audiences as active audiences interpret the discourse conveyed by the media. The theoretical approach used in this study is Reception Analysis. This study is descriptive qualitative research. Data were collected using Ferdinand de Saussures semiotics on six news articles of Serambi Indonesia throughout 2014 and in-depth interviews with eight female informants who were selected by purposive sampling technique. The results of the study illustrated that the dominant discourse in the media was women in Aceh were prone to violate Sharia. Findings also documented the tendency of informants to occupy oppositional reading positions that the way Serambi Indonesia covered Shariain Aceh was more likely to discriminate against women.